2015
DOI: 10.1155/2015/507909
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Enhanced MRI Scanning to Detect Cellular Inflammation in Experimental Chronic Renal Allograft Rejection

Abstract: Objectives. We investigated whether ultrasmall paramagnetic particles of iron oxide- (USPIO-) enhanced magnetic resonance imaging (MRI) can detect experimental chronic allograft damage in a murine renal allograft model. Materials and Methods. Two cohorts of mice underwent renal transplantation with either a syngeneic isograft or allograft kidney. MRI scanning was performed prior to and 48 hours after USPIO infusion using T2∗-weighted protocols. R2∗ values were calculated to indicate the degree of USPIO uptake.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…USPIO-enhanced T2* MRI has previously been used in man to assess cardiovascular inflammation in a range of different conditions,5–8 11 and preclinical models suggest this technique may be useful in assessing human patients with transplant rejection 4 13–17. In our cohort of stable patients with cardiac transplantation, we did not detect greater USPIO enhancement within the myocardium, but this contrasted with the increased measures of myocardial T2 found in transplant patients compared with volunteers.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…USPIO-enhanced T2* MRI has previously been used in man to assess cardiovascular inflammation in a range of different conditions,5–8 11 and preclinical models suggest this technique may be useful in assessing human patients with transplant rejection 4 13–17. In our cohort of stable patients with cardiac transplantation, we did not detect greater USPIO enhancement within the myocardium, but this contrasted with the increased measures of myocardial T2 found in transplant patients compared with volunteers.…”
Section: Discussioncontrasting
confidence: 57%
“…Promising preclinical studies have shown USPIO-enhanced MRI is able to detect acute cardiac and renal allograft rejection with USPIO signal correlating with macrophage distribution, rejection severity on histology and impaired cardiac function. Moreover, this approach can also be used to assess treatment response with rodent models demonstrating less USPIO enhancement following initiation of immunosuppression 4 13–17. A future role of USPIOs includes a ‘theranostic’ strategy whereby imaging is combined with therapy; Guo et al 18 recently conjugated an iron nanoparticle to a CD-3 antibody and a therapy gene, allowing imaging and targeting of T cells that play a central role in acute cardiac allograft rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, targeting of macrophages (usually total population or M1 fraction) has been pursued in preclinical imaging of several diseases by MRI, either by passive labeling or by active targeting of membrane receptors with vectorized nanoprobes 18 - 21 . Tracking of macrophage infiltration by MRI has been employed in models of kidney transplantation, fibrosis and ischemia-reperfusion 22 - 26 . Recent studies have been designed to detect M1/M2 macrophage polarization by MRI in animal models 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%